Performance of Floating Constructed Wetland in Reducing Phosphate and Nitrate Using Typha latifolia - Vina Namira Callysta Siregar; Harmin Sulistiyaning Titah; Bieby Voijant Tangahu; Ipung Fitri Purwanti; Mashudi Mashudi; Sarwoko Mangkoedihardjo; Isra Abdulwahab Al-Baldawi (3BIO: Journal of Biological Science, Technology and Management, 2026)
Pollution in rivers is caused by the direct discharge of untreated domestic waste, which is characterised by excessive foam on the water surface. This occurs due to relatively rapid population growth accompanied by limited waste management infrastructure, leading to river water pollution in Indonesia. Therefore, an effective, efficient, environmentally friendly, and low-cost solution is needed, such as a Floating Constructed Wetland (FCW) system using aquatic plants. In this study, the aquatic plant used was Typha latifolia, which was able to treat polluted water in the Kalidami River, Surabaya. The objective of this study was to determine the percentage reduction efficiency of each treatment for phosphate and nitrate in contaminated river water. This study evaluated the performance of a laboratory-scale floating constructed wetland planted with Typha latifolia for reducing phosphate, nitrate, and total suspended solids (TSS) in river water. The experiment was conducted using a batch system, and water quality parameters were monitored during the treatment period to assess pollutant removal efficiency.  The results showed that the floating constructed wetlands system with single T. latifolia plants reduced phosphate by 40%, nitrate by 27%, and TSS 36.00%. FCWs technology with this plant is quite efficient in improving the quality of domestic wastewater before it is directly discharged into the river.